Diseño, construcción y desarrollo de un filtro biológico para las aguas contaminadas con cromo: estudio de caso (2016)
Effective technology is required to remove contaminants present in water, which has caused the development of removal techniques over the past decades. Currently, absorption is believed to be the most simple and effective method for wastewater treatment, in which its success is dependent on the development of efficient absorbents. In the following case study, a crushed biological filter, containing Eichhornia crassipes and zeolites as supporting materials, was designed, developed, and put into practice. Eichhornia crassipes is an abundant aquatic plant in wetlands, lakes and river, causing it to create many environmental and ecological issues. Zeolites are also abundant and easy to obtain. The effectiveness of this filter in chromium removal was proven in this case study, making it a probable wastewater treatment technique due to its low cost and easy assembly.